Use of a Smartphone Application to Speed Up Interhospital Transfer of Acute Ischemic Stroke Patients for Thrombectomy - Tsai, Sheng-Ta; Wang, Wei-Chun; Lin, Yu-Ting; Huang, Wei-Shih; Huang, Hung-Yu; Wang, Chun-Ju; Lin, En-Zu; Kung, Wei-Ling; Guo, Yuh-Cherng; Lin, Kang-Hsu; Lu, Ming-Kuei; Yen, Pao-Sheng; et al. (Frontiers in Neurology, 2021)
Background In most countries, large cerebral artery occlusion is identified as the leading cause of disability. In 2015, five large-scale clinical trials confirmed the benefit of intra-arterial thrombectomy. However, thrombectomy is a highly technical and facility-dependent procedure. Primary stroke centers need to transfer patients to comprehensive stroke centers to perform thrombectomy. The time-lapse during interhospital transfer would decrease the chance of the patient’s proper recovery. Communication barriers also contribute to this delay. Aims We used a smartphone application to overcome communication barriers between hospitals. We aimed to shorten the door-to-puncture time of interhospital transfer patients. Methods We began using a smartphone application, “LINE,” to facilitate interhospital communication on May 01, 2018. We carried out retrospective data analyses for all the transfer patients (n = 351), with the primary outcome being the door-to-puncture time in our comprehensive stroke center (China Medical University Hospital). We compared the three periods: May 01 to Dec 31, 2017 (before the use of the smartphone application); May 01 to Dec 31, 2018 (the first year of using the smartphone application); and May 01 to Dec 31, 2019 (the second year of using the smartphone application). We also compared the transfer data with non-transfer thrombectomies in the same period. Results We compared 2017, 2018, and 2019 data. The total number of transfer patients was increasing over the years: 63, 113, 175, respectively. The mean door-to-puncture time decreased significantly, going from 109, through 102, to 92 minutes. Meanwhile, the mean door-to-puncture time in non-transfer patients were 140.3, 122.1, and 129.3 minutes. The main reason of time saving was the change of the way of communication, from point-to-point interhospital communication to hub-to-spoke interhospital communication. Conclusions We used this smartphone application to enhance interhospital communication, changed from the point-to-point to hub-to-spoke method. It made us overcome the communication barrier and build up interhospital connestion. And thus shortened the door-to-puncture time. Our experience demonstrated the importance of close communication and teamwork in hyperacute stroke care, especially in interhospital transfer for thrombectomy.